Planning time-optimal and smooth trajectories under kinodynamic constraints - Edgar, Leonardo (Nanyang Technological University, 2021)
Planning a time-optimized, smooth, and collision-free trajectory for robot manipulators subject to kinodynamic constraints is vital to increase the productivity of automation systems in the industry. With the benefit of a recent approach to Time-Optimal Path Parametrization based on Reachability Analysis (TOPP-RA), which is proven to be efficient and robust, this paper proposes a shortcutting heuristic that uses TOPP-RA to produce a fast yet smooth trajectory while satisfying the robot’s kinodynamic constraints. The algorithm is deployed to a four-degree-of-freedom Barrett Whole-Arm Manipulator in OpenRAVE. It is compared to the state-of-the-art shortcutting method based on parabolas and straight lines. The results show that the proposed shortcutting algorithm is robust and capable of producing efficient trajectories while satisfying the robot’s kinodynamic constraints.